1999
DOI: 10.1177/039139889902201008
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Improved Survival Time in Pigs with Complete Liver Ischemia Treated with a Novel Bioartificial Liver

Abstract: Aim of the study was to evaluate treatment efficacy and safety of a scaled-up version of our porcine hepatocytes based BAL system in pigs with complete liver ischemia (LIS). Thirty-one pigs underwent total devascularization of the liver (LIS) by termino-lateral porta-caval shunts and sutures around the bile duct, the common hepatic and gastroduodenal arteries and their accessory branches. The hepato-duodenal ligament was completely transected. Four experimental groups were studied: the first control group (LIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 12 publications
0
37
1
Order By: Relevance
“…The development of these devices has been approached in two very different ways. In one, the aim is to provide all the functions of the normal liver by the use of living liver cells with either human hepatic cells as in the Extra Corporeal Liver Assist Device (ELAD) [81] or porcine hepatocytes as in the Bio-artificial Liver device [82] and in various other European devices being developed in the Netherlands [83] and Germany [84]. Human primary hepatocytes are both difficult to procure and culture.…”
Section: Conclusion and Use Of Extracorporeal 'Liver Support Devices'mentioning
confidence: 99%
“…The development of these devices has been approached in two very different ways. In one, the aim is to provide all the functions of the normal liver by the use of living liver cells with either human hepatic cells as in the Extra Corporeal Liver Assist Device (ELAD) [81] or porcine hepatocytes as in the Bio-artificial Liver device [82] and in various other European devices being developed in the Netherlands [83] and Germany [84]. Human primary hepatocytes are both difficult to procure and culture.…”
Section: Conclusion and Use Of Extracorporeal 'Liver Support Devices'mentioning
confidence: 99%
“…In many different models of ALF several BALs based on animal liver cells have shown to prolong survival significantly in comparison to standard treatment [23][24][25][26][27][28][29][30][31][32][33] .…”
Section: How Good Are Results In Experimental Animals?mentioning
confidence: 99%
“…In this context, our studies have shown that in vivo-like quantitative as well as qualitative performance could be achieved in vitro using pharmaceutical drugs as test candidates (Bader et al 1992(Bader et al , 1996(Bader et al , 1998Langsch and Bader 2001). Currently, rat and human hepatocytes are being successfully cultured on novel modified polyetheretherketone membranes Nyberg et al (1992aNyberg et al ( , c, 1993Nyberg et al ( , 1996Nyberg et al ( , 1999 Pig Immunoisolation pig, rabbit, rat Jauregui et al (1994Jauregui et al ( , 1995 Protection against viral infection in humans by xenogeneic cells Gerlach (1996) In vivo-like microenvironment Ellis et al (1996) Protection from shear stress Flendrig et al (1997Flendrig et al ( , 1999 Ease of scale-up (PEEK-WC and PEEK-WE-polyurethane) which have been proposed to be promising biomaterials in liver support systems (De Bartolo et al 2004). The use of a flat membrane bioreactor as an extracorporeal liver support system, however, is accompanied by some disadvantages, such as the potential large dead volume and the low surface area-to volume ratio, as well as providing limited protection against viral infection by xenogeneic cells (depending on the molecular weight cut-off of the membranes used).…”
Section: Flat Membrane Systemsmentioning
confidence: 99%
“…Various liver support systems have been preclinically and clinically examined for their in vivo performance to date. In preclinical testing with liver support systems, significant improvement of survival time in hepatectomized animals or animals with moderate to severe liver failure could be achieved (Jauregui et al 1995;Dixit and Gitnick 1998;Flendrig et al 1999;Shito et al 2003;Yamashita et al 2003;Fruhauf et al 2004). However, it is difficult to assess and compare the efficacy of these systems, in part because of the heterogeneity of the animal models used.…”
Section: Liver Support Systems In Preclinical and Clinical Testmentioning
confidence: 99%